Global crop yield reductions due to surface ozone exposure: 2. Year 2030 potential crop production losses and economic damage under two scenarios of O₃ pollution - Avnery, Shiri; Mauzerall, Denise L; Liu, Junfeng; Horowitz, Larry W (Atmospheric environment (1994), 2011)
We examine the potential global risk of increasing surface ozone (O₃) exposure to three key staple crops (soybean, maize, and wheat) in the near future (year 2030) according to two trajectories of O₃ pollution: the Intergovernmental Panel on Climate Change Special Report on Emissions Scenarios (IPCC SRES) A2 and B1 storylines, which represent upper- and lower-boundary projections, respectively, of most O₃ precursor emissions in 2030. We use simulated hourly O₃ concentrations from the Model for Ozone and Related Chemical Tracers version 2.4 (MOZART-2), satellite-derived datasets of agricultural production, and field-based concentration:response relationships to calculate crop yield reductions resulting from O₃ exposure. We then calculate the associated crop production losses and their economic value. We compare our results to the estimated impact of O₃ on global agriculture in the year 2000, which we assessed in our companion paper [Avnery et al., 2011]. In the A2 scenario we find global year 2030 yield loss of wheat due to O₃ exposure ranges from 5.4 to 26% (a further reduction in yield of +1.5–10% from year 2000 values), 15–19% for soybean (reduction of +0.9–11%), and 4.4–8.7% for maize (reduction of +2.1–3.2%) depending on the metric used, with total global agricultural losses worth $17–35 billion USD₂₀₀₀ annually (an increase of +$6–17 billion in losses from 2000). Under the B1 scenario, we project less severe but still substantial reductions in yields in 2030: 4.0–17% for wheat (a further decrease in yield of +0.1–1.8% from 2000), 9.5–15% for soybean (decrease of +0.7–1.0%), and 2.5–6.0% for maize (decrease of + 0.3–0.5%), with total losses worth $12–21 billion annually (an increase of +$1–3 billion in losses from 2000). Because our analysis uses crop data from the year 2000, which likely underestimates agricultural production in 2030 due to the need to feed a population increasing from approximately 6 to 8 billion people between 2000 and 2030, our calculations of crop production and economic losses are highly conservative. Our results suggest that O₃ pollution poses a growing threat to global food security even under an optimistic scenario of future ozone precursor emissions. Further efforts to reduce surface O₃ concentrations thus provide an excellent opportunity to increase global grain yields without the environmental degradation associated with additional fertilizer application or land cultivation.